Knowledge Management System Development Using Tiwana Roadmap and Agile Scrum at HP Service Center Denpasar (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2026)
This study aims to design and develop a Knowledge Management System (KMS) at HP Service Center Denpasar by integrating the Tiwana Roadmap framework and the Agile Scrum development method. HP Service Center Denpasar faces challenges in knowledge retention and dissemination, where valuable knowledge assets, both tacit and explicit knowledge, are still stored individually. Therefore, this study focuses on documenting all knowledge possessed by various operational units, ranging from Senior PC/Laptop Technicians and Printer Technicians to logistics staff, in order to prevent knowledge loss and accelerate the knowledge transfer process. In the development process, the Tiwana Roadmap was selected as the main framework because of its ability to provide structured, systematic, and gradual guidance for identifying, managing, auditing, and optimally utilizing organizational knowledge. Meanwhile, to execute the blueprint into software form, the Agile Scrum method was implemented to support a system development process that is flexible, adaptive, and responsive to changing requirements and dynamic field conditions through iterative sprint cycles. After the system has been developed, the testing phase will be conducted using two comparative approaches: the User Experience Questionnaire (UEQ) to quantitatively measure user experience aspects, and Cognitive Walkthrough / Cognitive Task Analysis (CTA) to evaluate cognitive efficiency and system usability when used by staff. The expected final result of this study is a KMS platform that is not only technically valid but also interactive and capable of improving operational efficiency at HP Service Center Denpasar.